Study of asphalt pavement deterioration through remote sensing - Nikolaou, Andreas (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2016)
Asphalt pavement surface is a very important parameter of the transportation infrastructure assessment. Due to the high cost of asphalt pavements and the hazard of the pavements that are in bad condition, many studies focused on how can asphalt road pavements be monitored and mapped and also identify the best remote sensing methods for the structural damages that were presented. When the deteriorations of asphalt pavements, such as potholes, cracks, raveling, rutting and others, which were caused from natural and physical conditions, are detected, the government authorities and road agencies can develop maintenance plans. This study examines in depth different methods and techniques of remote sensing. Also, this study is based on research that will represent a large number of literature reviews from studies. Moreover, the deterioration of asphalt is explained in one of the following chapters. Most of the authors emphasized on that most remote sensing techniques are cost effective and need much less time to be studied. Remote sensing methods can give continues observation and reduce risks and hazards as well. The literature review was based on the methods of remote sensing that the researchers used, in order to detect the different methods of asphalt pavements. Furthermore, the results of this research study showed that the most used method is the spectral library and then the satellite sensors. In addition, most studies were made for the cracked area of asphalt and also for mapping the conditions of asphalted road pavements. Finally, the results of this research study showed that the remote sensing methods are a useful tool for transportation infrastructure assessments, both, for monitoring the condition of asphalt pavement and detecting structural damages of asphalt.
Keywords: Asphalt pavement; Transportation infrastructure assessment